Qualities of broiler litter in ruminant feeding (2005)
Feed represent a major proportion of the overall production cost in the livestock industry. Availability of good quality and unadulterated conventional feed all year round is a major constraint in livestock production. Also, competition for the same feed resources existing between humans and animals have further compounded the problem leading to overpricing of animal products. Poultry wastes, if properly processed represent a vast reservoir of cheap nutrients especially for ruminants. This study was designed to evaluate broiler litter as a feed for ruminant diets. One hundred and twenty (120) broiler chicks were randomly distributed into three treatments of forty birds each. The birds were fed diets containing 25% crude protein and 23% crude protein at the starter and finisher phases. Litter collected on days 35, 42 and 49 after stocking were sun dried and subjected to proximate analysis to determine crude protein (CP), neutral detergent fibre (NDF) and acid detergent fibre (ADF). The CP, NDF and ADF were: 22.5%, 25.5% and 23.5% for CP, 40.5%, 38.2% and 39.3% for NDF and 21.4%, 20.3% and 20.8% for ADF respectively. However, there were no significant differences (P< 0.05) in the CP and ADF values for the 3 stages of collection. Broiler litter has high protein level which will be efficiently utilized to promote optimum weight gain in ruminants.